2015
DOI: 10.1111/jpn.12409
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and the feline gut microbiome – a pilot study

Abstract: Compared with lean humans, the gut microbiota is altered in the obese. Whether these changes are due to an obesogenic diet, and whether the microbiota contributes to adiposity is currently discussed. In the cat population, where obesity is also prevalent, gut microbiome changes associated with obesity have not been studied. Consequently, the aim of this study was to compare the gut microbiota of lean cats, with that of overweight and obese cats. Seventy-seven rescue-shelter cats housed for ≥3 consecutive days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
2
29
0
2
Order By: Relevance
“…Plausible explanations for the association include a change in gut microbiome (Kieler et al . ) and dysfunction of adipokine secretion, which is known to increase the risk of food allergies and other immune‐mediated gastrointestinal diseases (Hersoug & Linneberg ), such as inflammatory bowel disease (Michalak et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plausible explanations for the association include a change in gut microbiome (Kieler et al . ) and dysfunction of adipokine secretion, which is known to increase the risk of food allergies and other immune‐mediated gastrointestinal diseases (Hersoug & Linneberg ), such as inflammatory bowel disease (Michalak et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…However, among all the gastrointestinal signs examined in the current study, only diarrhoea showed significantly increased odds with BCS. Plausible explanations for the association include a change in gut microbiome (Kieler et al 2016) and dysfunction of adipokine secretion, which is known to increase the risk of food allergies and other immunemediated gastrointestinal dis eases (Hersoug & Linneberg 2007), such as inflammatory bowel disease (Michalak et al 2016). Scarlett & Donoghue (1998), on the other hand, identified diarrhoea as a risk factor for under weight in cats.…”
Section: Oral and Gastrointestinal Conditionsmentioning
confidence: 99%
“…Recent 16S rDNA sequencing studies of fecal samples from obese humans, including 1 study of 154 mothers and twins with obese and lean phenotypes, reveal that human obesity is also associated with decreased diversity and lower proportions of fecal Bacteroidete s and that weight loss is associated with a proportional increase in Bacteroidetes . Similarly, obese cats have lower proportions of Bacteroidetes than healthy cats, a feature of moderately and severely obese cats, suggesting that changes in the microbiome occur before clinically relevant obesity is apparent . A single study comparing lean and obese pet dogs did not identify large shifts in the microbiome associated with obesity .…”
Section: Microbe‐host Interactions and Associations Between Dysbiosismentioning
confidence: 98%
“…A large number of articles are steadily being published showing the extent (e.g., in microbial composition) and consequences (e.g., relationship of specific microbes with persistence of clinical signs) of this symbiosis in health and during a variety of disease states and conditions such as obesity, gastrointestinal inflammation, and diarrhea (Deusch et al, 2015; Guard et al, 2015; Hand et al, 2013; Handl et al, 2013; Junginger et al, 2014; Kieler et al, 2016; Minamoto et al, 2014; Minamoto et al, 2015; Song et al, 2013; Suchodolski et al, 2015). These studies are supported by meta’omic analytic techniques (Morgan & Huttenhower, 2014) and powerful freely-available computational resources to analyze the generated data (Navas-Molina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%